THE INFLUENCE OF INDEPENDENCE AND LEARNING STYLE ON MATH PROBLEM-SOLVING ABILITY - Naiborhu, Rusdin; Ronaldo Kho; Wahyudi, Irfan (Master of Science Education Program, Postgraduate Program of Cenderawasih University, 2025)
This study aims to analyze the influence of self-regulated learning and learning styles on the mathematical problem-solving abilities of students at SMA Negeri Ilugua, Mamberamo Tengah Regency, Papua Pegunungan Province. A quantitative approach with a survey design was used. The population consisted of all students at SMA Negeri Ilugua, and the sample included 102 students selected through simple random sampling. Data were collected using an essay-based mathematics problem-solving test and questionnaires to measure self-regulated learning and learning styles. The findings show that: (1) self-regulated learning has a significant effect on students' mathematical problem-solving ability, contributing 48.5% to the variance; (2) learning styles significantly influence problem-solving ability, with kinesthetic learners achieving the highest scores, followed by auditory learners, while visual learners had the lowest; (3) simultaneously, self-regulated learning and learning styles have a significant combined effect, contributing 59.9% to the improvement of problem-solving abilities. These results emphasize the importance of promoting self-regulated learning and tailoring instructional strategies to students' learning styles to enhance mathematical problem-solving skills, particularly in remote regions such as Papua. The study suggests that adaptive learning approaches and stronger interventions to develop learner autonomy are essential for improving educational outcomes.